Evaluasi Supplier Ban Trailer di PT. X menggunakan Metode Analytic Hierarchy Process (AHP) - Cherry Chandra; Herri Christian Palit (Jurnal Titra, 2022)
Supplier evaluation is a method that is used by companies, including PT. X to ensure that the supplier had been used in accordance with the desired standard. PT. X is a shipping company that serves shipping containers throughout Indonesia, especially in eastern Indonesia. In its operations, PT. X needs trailer tires as truck tires used to transport containers from and to the port where the ship rests. The evaluation of supplier assessment conducted by the previous purchasing department still tends to be subjective and there is no definite method. So that in this study an evaluation of supplier assessment was carried out using the analytic hierarchy process method. The AHP method helps companies make decisions by comparing the level of importance of each assessment criteria and sub-criteria. The value of the level of importance will then be processed using Microsoft Excel to get the weight of the assessment used in the supplier assessment form. In research that uses the AHP method, the final result is the best supplier, the supplier with the highest final value, namely supplier 1.